Psycho-Social Approach in Developing the Empowerment Model for Poor Communities with Disabilities in East Java: Pendekatan Psiko-Sosial untuk Memberdayakan Masyarakat Miskin Penyandang Disabilitas - Ani Putra, Muhammad Ghazali Bagus (Universitas Muhammadiyah Sidoarjo, 2025)
There are many models of community empowerment but few are based on a psycho-social approach. Even though the psycho-social approach to empowering poor people with disabilities will be able to understand the psycho-social aspects of the people with disabilities who will be empowered. This study aims to analyze the role of the psycho-social approach in developing a model for empowering poor people with disabilities in East Java. The approach in this research is qualitative with the type of instrumental case study with the aim that the case under study will be a model for other cases. There were 8 interview participants who were involved in this study, consisting of 2 representatives from Bapemas East Java, 2 representatives from Bapemas Sidoarjo Regency and 4 representatives from the Joint Business Group (KUBE) whose members are persons with disabilities who are economically disadvantaged. Interview data were analyzed using thematic analysis so as to collect the role of psychology which became the basis for developing the empowerment model, namely social initiative (cognitive), synergy (affective) and sustainability (conative). This empowerment model was then developed by involving the role of a psycho-social approach to equip less well-off persons with disabilities to be more independent and have an economic impact on the surrounding community.